Money Politics: An Islamic Economic Perspective (A Case Study of Regional Head Elections in Indonesia) - Miftahur Rohmah; Nur Ina Avia; Wildan Setiawan; Mashudi (Penerbit Hellow Pustaka, 2025)
This research examines the phenomenon of money politics in regional head elections in Indonesia from the perspective of Islamic economics. Money politics refers to the practice of providing financial or material incentives to voters in order to influence their choices. This practice not only contradicts the principles of a healthy democracy but also violates the values of Islamic economics, which prioritize justice, transparency, and social responsibility. In Islamic economics, transactions or actions that lead to injustice, manipulation, and social harm are strictly prohibited (haram) because they threaten the balance and harmony within society. This study employs a qualitative approach using a case study method, in which data were collected through interviews, observations, and documentation related to cases of regional head elections in Indonesia involving money politics practices. The research findings reveal that money politics distorts the electoral process, results in the election of low-quality leaders, and weakens political legitimacy in society. From the perspective of Islamic economics, money politics undermines the moral and spiritual integrity of society because it encourages voters to act dishonestly and neglect their moral responsibilities. The implications of this research suggest the implementation of stricter preventive measures in election monitoring, more in-depth political education based on Islamic values, and the strict enforcement of laws against money politics perpetrators. This study highlights the importance of the role of Islamic economics in strengthening ethics in political life and rejecting practices that cause harm to the wider community.